Twenty over eighty : conversations on a lifetime in architecture and design - Kwun, Aileen; Kwun, Aileen, 1985-; Smith, Bryn (2016)
"Twenty Over Eighty features profiles and interviews with twenty creative professionals over the age of eighty who have dedicated their lifetimes to design. In revealing conversations with creative minds from a broad variety of fields--from architecture and advertising to furniture, product, industrial, and graphic design--design writers Aileen Kwun and Bryn Smith spotlight makers and thinkers who continue to experiment, innovate, and make vital contributions to their disciplines well into their eighth decade. Twenty Over Eighty is not only a record of their remarkable histories and experiences, but also a source of knowledge and inspiration for contemporary creatives and generations of designers to come"--
Keywords: Older designers -- Biography; Older designers -- Interviews; DESIGN / General